2022
DOI: 10.1136/bmjopen-2021-057681
|View full text |Cite
|
Sign up to set email alerts
|

Individual and contextual factors associated with maternal healthcare utilisation in Mali: a cross-sectional study using Demographic and Health Survey data

Abstract: ObjectiveWe examined the national prevalence as well as the individual and contextual factors associated with maternal healthcare utilisation in Mali.SettingThe study was conducted in Mali.ParticipantsWe analysed data on 6335 women aged 15–49 years from Mali’s 2018 Demographic and Health Survey.Outcome variableMaternal healthcare utilisation comprising antenatal care (ANC) attendant, skilled birth attendant (SBA), and postnatal care (PNC) attendant, was our outcome variable.ResultsPrevalence of maternal health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 85 publications
1
4
0
1
Order By: Relevance
“…Ever married women were more likely to partially and adequately utilize health services compared to never married women. This has been reported in other studies and the reason provided in this regard is that married women tend to enjoy financial support from their husbands [ 38 , 39 ]. Employment status is another factor which contributes significantly to health services utilization.…”
Section: Discussionsupporting
confidence: 69%
“…Ever married women were more likely to partially and adequately utilize health services compared to never married women. This has been reported in other studies and the reason provided in this regard is that married women tend to enjoy financial support from their husbands [ 38 , 39 ]. Employment status is another factor which contributes significantly to health services utilization.…”
Section: Discussionsupporting
confidence: 69%
“…Our results differ from previous studies, which found overall positive associations between ANC and PNC in Ethiopia, Nigeria, and Uganda [ 19 , 25 27 ]. However, prior studies have also demonstrated that rurality is negatively associated with PNC in sub-Saharan Africa [ 11 , 21 ]. Since 652 (44.7%) of our participants do not reside in Mbarara district, indicating they likely reside in rural settings, this could partially explain differences between our results and prior studies.…”
Section: Discussionmentioning
confidence: 99%
“…All regressions were adjusted for the following participant characteristics: (1) age, (2) marital status at time of delivery, (3) parity, (4) residence in Mbarara, (5) referral to MRRH for delivery, and (6) HIV serostatus. Covariates were selected a priori based upon their relationships with the exposure variable and outcome of interest [ 11 , 19 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…The literature showed that monitoring inequalities are needed to address unfair disparities, identify vulnerable population subgroups left behind, and help inform equity-oriented policies that can narrow existing inequalities (3). Worldwide, evidence has accumulated on disparities in receiving competent maternal health care services by many dimensions of inequality, including wealth quintiles, location, education, maternal age, and women's empowerment (4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%